2020
DOI: 10.1155/2020/3607436
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of BMPER in Ovarian Cancer and the Mechanism by which It Promotes Malignant Biological Behavior in Tumor Cells

Abstract: Background. BMPER has been reported to be associated with the biological behavior of a few malignant tumors, but the mechanism is still unclear. We aimed to detect BMPER expression in ovarian epithelial tumor tissues and its effects on their biological behaviors, as well as to elucidate the possible mechanism. Methods. BMPER expression in ovarian epithelial tumor tissues was detected by immunohistochemistry. BMPER expression in ovarian cancer cell lines was inhibited via RNA interference. Changes in the malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The suppression of BMPER inhibits the migration, invasion and proliferation of OC, and promotes apoptosis. In that study, the researchers considered that BMPER may become a potential prognostic marker and that modification of this pathway may change the role of BMPER in promoting the malignant biological behavior of ovarian cancer cells [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…The suppression of BMPER inhibits the migration, invasion and proliferation of OC, and promotes apoptosis. In that study, the researchers considered that BMPER may become a potential prognostic marker and that modification of this pathway may change the role of BMPER in promoting the malignant biological behavior of ovarian cancer cells [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…BMPER binds to BMP and regulates TGF-β/BMP signaling. Previous studies have linked BMPER to lung cancer and ovarian cancer [ 34 , 35 ], and it has been shown that BMPER expression is controlled by methylation at the transcriptional level. Treatment with 5-aza-dC can reduce BMPER expression in fibroblasts and mitigate invasion and migration of idiopathic pulmonary fibrosis lung fibroblasts [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have linked BMPER to lung cancer and ovarian cancer [ 34 , 35 ], and it has been shown that BMPER expression is controlled by methylation at the transcriptional level. Treatment with 5-aza-dC can reduce BMPER expression in fibroblasts and mitigate invasion and migration of idiopathic pulmonary fibrosis lung fibroblasts [ 35 ]. In our study, we observed a positive correlation between hypermethylation of cg17561435 in BMPER and the HPSM risk score, suggesting that BMPER hypermethylation may be closely associated with poor prognosis in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Mainly adopted to treat the disease at the initial period and long term treatment, esomeprazole could be taken for the long term maintenance treatment of esophagitis and symptomatic treatment of gastroesophageal reflux disease. It could prevent the recurrence of the esophageal reflux disease efficiently, but there are few studies on the role of PPI on the hepatoma cell [10] .…”
Section: Group N Inhibition Ratio (%) 24 H 48 H 72 Hmentioning
confidence: 99%